Insect-based compost and vermicompost production, quality and performance. Issue 1 (7th February 2020) - Piñero, Jaime C.; Shivers, Traron; Byers, Patrick L.; Johnson, Hwei-Yiing
Abstract: In an attempt to utilize large amounts of Japanese beetles, Popillia japonica (Coleoptera: Scarabaeidae) that were captured using a mass trapping system, compost using Japanese beetle carcasses was prepared with the layer method. Carbon sources included shredded paper, wood chips and leaves, while the sole nitrogen source was frozen Japanese beetles. In addition, Japanese beetle-based vermicompost was prepared in the greenhouse by mixing the Japanese beetle-based compost with sphagnum peat moss and moist shredded paper and exposing this mixture to composting earthworms ( Eisenia fetida ). Chemical analyses of the Japanese beetle carcasses indicated that 10.8% of their body weight is nitrogen (N). Analyses of the resulting Japanese beetle-based compost and vermicompost indicated that both types of materials are good quality soil amendments. Greenhouse studies were conducted to quantify the effects of varying proportions of Japanese beetle-based vermicompost and compost mixed with a potting medium and varying dosages of synthetic fertilizer 20-0-0, on mean fresh and dry weight of lettuce shoots and leaf area. Japanese beetle-based compost and vermicompost increased lettuce biomass to an extent that was comparable with the addition of synthetic N-based fertilizer. A mixture of 15 and 30% of each compost type with potting media significantly increased plant weight and leaf area compared with potting medium alone. Results indicate that composting and vermicomposting insect carcasses are a simple, effective and affordable method to augment fertilization in support of organic production.